Identification of NLRP3PYD Homo-Oligomerization Inhibitors with Anti-Inflammatory Activity - Ghafary, Soroush Moasses; Soriano-Teruel, Paula M.; Karami, Fatemeh; Barigye, Stephen J.; Fernández-Pérez, Iván (International Journal of Molecular Sciences, 2022)
Inflammasomes are multiprotein complexes that represent critical elements of the inflammatory response. The dysregulation of the best-characterized complex, the NLRP3 inflammasome, has been linked to the pathogenesis of diseases such as multiple sclerosis, type 2 diabetes mellitus, Alzheimer’s disease, and cancer. While there exist molecular inhibitors specific for the various components of inflammasome complexes, no currently reported inhibitors specifically target NLRP3PYD homo-oligomerization. In the present study, we describe the identification of QM380 and QM381 as NLRP3PYD homo-oligomerization inhibitors after screening small molecules from the MyriaScreen library using a split-luciferase complementation assay. Our results demonstrate that these NLRP3PYD inhibitors interfere with ASC speck formation, inhibit pro-inflammatory cytokine IL1-β release, and decrease pyroptotic cell death. We employed spectroscopic techniques and computational docking analyses with QM380 and QM381 and the PYD domain to confirm the experimental results and predict possible mechanisms underlying the inhibition of NLRP3PYD homo-interactions.
Keywords: inflammasome inhibitors; NLRP3; screening; split-luciferase; pyroptosis